Tingkat Insidensi Malaria di Wilayah Pemanasan Kelambu Berinsektisida Tahan Lama dan Wilayah Kontrol (MALARIA INCIDENCE RATE OF HEAT ASSISTED REGENERATION LONG LASTING INSECTICIDAL NETS AREA AND CONTROL) - Sudarnika, Etih; Sudarwanto, Mirnawati; Saefuddin, Asep; Cahyaningsih, Umi; Hadi, Upik Kesumawati; Kusriastuti, Rita; Eng, Jodi Vanden; Zhang, Daowen; Hawley, William A. (Jurnal Veteriner; Vol 12 No 1 (2011), 2012)
Long lasting insecticidal nets (LLIN) is one effective way to prevent malaria. Permethrin treatedLLIN is one type of LLIN which is recommended by WHO. Several studies have shown that these types ofLLIN requiring heat assisted regeneration after washing to enhance the biological activity of insecticidethat contained in the LLIN fibers. This study aimed to compare the incidence rates of malaria in childrenunder five years old who live in the intervention area (where the heat assisted regeneration on LLIN afterwashing was applied) and control area (where the heat assisted regeneration on LLIN after washing wasnot applied). Data of malaria cases was collected from laboratory log book at all health centers in BangkaDistrict, in the period of June June 2007 until July 2008. Data were analyzed with Poisson regressionmodels. The results showed that the incidence rate of malaria in children under five years old was notsignificantly different between the treatment and control areas.
Keywords: heat assisted regeneration, incidence rate, Olyset®, permethrin treated LLIN, Poisson Regression Model.